First Occurrence of Three Species of the Genus Dactylogyrus Diesing , 1850 (Monogenea: Dactylogyridae) in Iraq from Some Diyala River Fishes , Diyala Province - Al-Saadi, Abid Ali J. J.; Mohammed, Haider J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Three monogeneans: Dactylogyrus folkmanovae from gills of Chondrostoma regium, D. reinii from gills of Mesopotamichthys sharpeyi and D. robustus from gills of Leuciscus vorax were collected from Diyala River in Diyala Province. The description, measurements and illustrations of these parasites were given.